REALIZING GREEN SCHOOL AT INSAN KAMIL NATURE SCHOOL WITH CONCEPTUAL MODEL - Fachri Fachri; Wahyuddin Naro; Muzakkir Muzakkir; Muh. Rapi (Jurnal Kajian Pendidikan dan Psikologi, 2024)
The purpose of this study is to reveal the realization of green schools in Insan Kamil Nature School with a conceptual model. This research is a qualitative descriptive research. This research uses a phenomenological approach. The primary data in this study is the school community at Insan Kamil Nature School, Gowa Regency. The Principal and Vice Principal, teachers, students, education personnel, and other officers at Insan Kamil Natural School, Gowa Regency are the primary data sources that will be observed and interviewed to collect data on the focus of the problem in the study. The secondary data in this study are books or documents related to the research theme, especially school documents (Insan Kamil Nature School Kabupaten Gowa) related to school policies in environmental management. Data collection techniques with observation, interviews, documentation studies, and Focus Group Discussions (FGD). The results showed that; Realizing a green school at Insan Kamil Nature School must fulfill the four main components of a green school, therefore the curriculum and learning activities of Insan Kamil Nature School must be in line with the main components of a green school by relying on 4 (four) pillars of the Insan Kamil Nature School curriculum, namely: moral development, logic, leadership, and entrepreneurship.